Improve the Performance Coefficient of a Heat Pump Soil_Water))Operating on the Principle of - ديبة جابر; بربهان سلمان (Latakia University Journal -Engineering Sciences Series, 2021)
Due to the increasing energy costs and the increasing interest in the environment, many studies have been conducted on various methods, especially in the field of the residential and agricultural sectors, and one of these methods is the use of both thermal energy and geothermal energy. Heat pumps operating on the principle of soil are desirable water when the external temperature is moderate, but when the external temperature decreases a lot, the value of the performance coefficient of the heat pump soil - water remains constant at certain values in summer and winter seasons. Due to the challenges resulting from the depletion of fossil fuels as well as global warming, it was necessary to improve the efficiency of the soil-water heat pump to meet the heating and air conditioning needs. In this research, the effect of piping on the work of a soil-water heat pump at a depth of 2 meters was studied, and the temperature of entry and exit of water was measured in the cases of condensation and evaporation, that is, when the ground temperature was higher or lower than the water entry temperature. The temperature of entry and exit of water and the flow of water can be measured for a period of three months in year 2020, after burial in the soil in heating, through the gradient by combining soil and wood panels. The temperature of the heat and the amount of heat in the air in a heat that reaches a certain temperature in the heat. The depth and its direct exit from the tube while the heat spread was greater when entering the water in the opposite direction.